Research on the operation mode of the gig economy market of Qingdao, China - Qingyu, Li (2020)
This dissertation aims to re-examine and discuss the development status of two different gig economy markets, "platform-based gig economy" and "offline gig economy" in Qingdao, China. So far, many studies have put forward many suggestions for the development of platform-based gig economy. However, there are still severe deficiencies in the research on the offline gig economy. This dissertation selects 20 gig workers from all walks of life in two different gig economy markets to conduct ethnographic field surveys and semi-structured interviews. After that, analysis methods such as coding and triangulation were used to triple-code the obtained data, and the survey results were compared and analyzed from the perspectives of investigators, gig workers, and platforms. Findings indicate that there are differences in workers' wages, employment rights options, and skill training in two different gig economy markets. Moreover, it further analyzes suggests that the reasons behind the differences from the aspects of flexibility, income, health reasons and work experience of gig jobs. The author hopes to solve the current problems in the gig market from the root. Therefore, this dissertation combines the situation of China's political system and the specific elements of Qingdao's gig market and then proposes a four-step model of establishing a more inclusive gig market internet platform. While ensuring that the platform is supervised and guided by the Qingdao government, it is also operated by enterprises, so that the platform takes into account fairness and efficiency. After discussing II the three primary characteristics of the platform, the author puts forward the problem of wage arrears, opaque identity information, opaque business information, and platform labour contracts solved by the platform. Keywords: The gig market in Qingdao, China, Platform-based gig economy, Offline gig economy, Motivation and reason for work, Internet trading platform